True bipolar or extended bipolar left ventricular pacing is associated with better survival in cardiac resynchronization therapy patients. Issue 4 (17th April 2020) - Kutyifa, Valentina; Jame, Sina; Wang, Paul J.; Musat, Dan; Jones, Paul; Wehrenberg, Scott; Stein, Kenneth
Abstract: Background: Limited studies are available on the clinical significance of left ventricular (LV) lead polarity in patients undergoing cardiac resynchronization therapy (CRT), with a recent study suggesting better outcomes with LV true bipolar pacing. Objective: We aimed to determine whether true bipolar LV pacing is associated with reduced mortality in a large, real‐life CRT cohort, followed by remote monitoring. Methods: We analyzed de‐identified device data from CRT patients followed by the Boston Scientific LATITUDE remote monitoring database system. Patients with LV bipolar leads paced between the LV ring and LV tip were identified as true bipolar and those with LV bipolar leads paced between LV tip or LV ring and right ventricular (RV) coil were identified as extended bipolar. Patients with unipolar leads were identified as unipolar. Results: Of the 59 046 patients included in the study, 2927 had unipolar pacing, 34 390 had extended bipolar pacing, and 21 729 had true bipolar pacing. LV true bipolar pacing was associated with a significant 30% lower risk of all‐cause mortality as compared to unipolar pacing (hazards ratio [HR] = 0.70, 95% CI: 0.62‐0.79, P  < .001), after adjustment for age, gender, LV lead impedance, LV pacing threshold, and BIV pacing percentage <95%. Extended bipolar LV pacing was also associated with 24% lower risk of all‐cause mortality when compared to unipolar LV pacing (HR = 0.76, 95% CI: 0.68‐0.85; P  < .001). However, there were no differences in outcomes between true bipolar and extended bipolar LV pacing (HR = 0.97, 95% CI: 0.93‐1.01; P  = .198). Conclusion: True bipolar or extended bipolar LV pacing is associated with a lower risk of mortality in CRT patients as compared to unipolar LV pacing.